Integration Portal of Arabic Language and Islamic Education in the Digital Era - Akzam, Ismail; Yunita, Yenni; Zubaidah (The International Journal of Education Management and Sociology, 2024)
The digital era has brought significant changes to the learning of the Arabic language and Islamic education. This study explores the potential and challenges of using an integration portal as an innovative solution in this context. Through a descriptive qualitative approach, involving literature review, content analysis of existing learning portals, and interviews with experts, this research identifies the key features of an effective integration portal, its benefits, and the challenges of implementation. The results show that the integration portal can enhance student motivation, learning efficiency, and access to quality materials. However, challenges such as resistance to change and infrastructure limitations need to be addressed. The integration of artificial intelligence (AI) opens new opportunities for personalized learning. This study concludes that the success of the integration portal lies in its ability to blend traditional values with technological innovation, and it suggests collaborative development and continuous evaluation to improve its effectiveness.